T-blocker: a simple and robust probe-free quantitative PCR assay to detect somatic mutations down to 0.1% frequency. (4th October 2018) - Kim, Hanyoup; Ruby, Aaron E; Shandilya, Harini G; Virmani, Arvind K; Rahman, Nandita; Strange, Christina M; Huuskonen, Jarkko
We have developed a simple and robust probe-free quantitative PCR (qPCR) assay method that can detect minor mutant alleles with a frequency as low as 0.1% in a heterogeneous sample by introducing a novel T-blocker concept to the allele-specific PCR method. Four new KRAS and BRAF mutation detection assays were developed and their performance was demonstrated by testing a large number of replicates, utilizing a customized PCR protocol. Highly efficient and specific mutant amplification in conjunction with selective wild-type suppression by the T-blocker concept enabled 0.1% detection sensitivity using the intercalating dye-based qPCR chemistry instead of more complex target-specific dye-labeled probes. Excellent consistency in sensitivity and specificity of the T-blocker assay concept was demonstrated.